Dampak Penggunaan Gawai Terhadap Perkembangan Karakter Siswa Di SD Negeri 4 Tiga - Amanda, Sang Ayu Putu Gita; Numertayasa, I Wayan; Astuti, Ni Putu Eni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
Excessive use of gadgets among Elementary School Students greatly affects their character development both in the school environment and in their daily lives. This study aims to describe the effect of gadget use on the development of students' character in terms of responsibility, caring, discipline and respect for students at Elementary School 4 Tiga. This type of research is qualitative with the Miles and Huberman data analysis method using observation, interview and questionnaire techniques. The research instruments used were observation sheets, interview guidelines and questionnaire distribution using Google form. The results of the first study showed that gadget use reduces students' responsibility in completing assignments and carrying out obligations. Second, students become less concerned about others, showing a tendency towards individualism. Third, gadget use causes decreased discipline, difficulty managing time, and decreased spiritual awareness. Fourth, students show decreased respect, communication ethics, and social skills. The impact of gadget use shows the importance of supervision and character development in the learning process.